Prototype Kran Wudhu Otomatis Berbasis Arduino Uno - Ramadhaningrum, Ramadhaningrum; Hidayatullah, Rahmat; F.Afidh, Reza Fahlevie (JOSTECH: Journal of Science and Technology, 2021)
The conventional ablution system has a weakness where the use of water is wasteful because humans forget to turn off the faucet or faucets that are easily damaged due to frequent use by humans. The purpose of the research is to make ablution easier, save water use and automate water faucets and tub filling. By utilizing an automatic ablution device with a distance sensor (ultrasonic sensor) as a human detector in taking ablution water and the control system is the Arduino Uno. The method used in this study is the waterfall method where in this method there are steps to work on the research, namely, needs analysis, tool design, tool making and coding, tool testing and tool implementation. In this study, it can be concluded that if the distance is 30 cm then the solenoid valve is active and water comes out, if the distance is > 30 cm then the solenoid valve is not active and the water does not flow and if the sensor distance to the water surface is 18 cm then the water pump will turn on. the sensor distance to the water surface is < 5 cm, the water pump will turn off